1918-1933, Raul Lino: ‘De re aedificatoria’ on ‘A Nossa Casa’, a specific and 'modern' treatise - Carla Garrido de Oliveira (Joelho)
Might it be possible to discern in Raul Lino's writings _namely those published in 1918 and 1933_ the profile of a modern treatise on architecture, in the early 20th century?Drawing parallels on Alberti's "inaugural" essay (Choay, [1980], p.25), an assay precept is outlined (‘pro tem’ less conceptual than it is pragmatic), with which to approach both Lino books, anent the design of the modern dwelling. From Choay's five teatrise-making hallmarks, a structural comparison is enacted between Vitruvius' and Alberti's treatises and those books of Raul Lino; from Krüger (2011), further benchmarks of form and schematics are highlighted, as are othersrelated to subject, objective and framework.Probing both publications under the "cost-effective, modern dwelling" design premise (Lino, 1933, p.51), the 1918 book flaunts, perhaps, a richer vitruvian undertone, and more akin to a "book […] on architecturalcomposition" (Vogliazzo, 1988-90)[1], featuring tips on construction, just as it were a practical handbook; the 1933 release, however, borders on albertine ‘inauguration’, and contends an artistic-architectural theory, encompassing of a system of ‘virtues’; the latter is almost a "commentator" (Choay, [1980]), paving the way to "protest" (Lino, 1933, p.96) in a time of criticism, and manifestos.[1] Vogliazzo holds that, "aside from Le Corbusier, the last books to truly focus on architectural composition" were written by Hermann Muthesius and Raul Lino (Vogliazzo, 1988-90, p.29); the correlation between Muthesius' and Lino's writings triggered an already ongoing comparison, akin to the present proposal;_Será possível reconhecer nos textos de Raul Lino, nomeadamente nos livros publicados em 1918 e 1933, características de um tratado de arquitectura moderno, a inícios do século XX?Estabelecendo paralelos com o texto “inaugural” de Alberti (Choay, [1980], p.25), elaboramos um princípio de análise, de momento mais funcional que de conceitos, destes dois livros de Raul Lino sobre a problemática do projecto da casa moderna. Partindo dos cinco verificadores de propriedade tratadística de Choay, estabelecemos uma comparação estrutural entre os tratados de Vitrúvio e de Alberti e estes textos de Raul Lino; a partir de Krüger (2011), sublinhamos outros aferidores de forma e sistemática, mas também de objecto, objectivo e enquadramento.Lavrando ambos no âmbito da teoria do projecto “da moderna casa económica” (Lino, 1933, p.51), será possível considerar que o livro de 1918 é mais vitruviano, próximo de um “livro […] de composição arquitectónica” (Vogliazzo, 1988-90)[1] com recomendações construtivas em jeito de manual prático; o livro de 1933 aproxima-se da ‘inauguração’ albertiana, propondo uma teoria artística-arquitectónica em torno de um sistema de ‘virtudes’; mas este último é também mais “comentador” (Choay,[1980]), abrindo passo ao “protesto”(Lino, 1933, p.96) em tempos de crítica e manifestos.[1] Vogliazzo considera que, “para além de Le Corbusier, os últimos verdadeiros livros de composição arquitectónica ”foram escritos por Hermann Muthesius e Raul Lino (Vogliazzo, 1988-90, p.29); a relação entre textos de Muthesius e Lino é mote para um paralelo, em desenvolvimento, análogo à presente proposta;